The impact of Gaza’s genocidal war: Scholasticide, trauma, and resilience among UCAS staff - Alhossary, Abeer Z.; ElMashharawi, Aya K. (Bulan Sabit Merah Indonesia, 2025)
Israel’s genocidal war on Gaza has profoundly disrupted the educational landscape, creating significant challenges for institutions such as the University College of Applied Sciences (UCAS). This study examines how Israel’s war on Gaza has affected UCAS staff, with particular attention to displacement, property loss, and psychological trauma. To address this objective, the study employed a quantitative survey approach to assess the extent of material and personal losses among academic and administrative personnel. Analysis of data from 192 staff members revealed that 93% experienced displacement, 53% lost all property, and 43% lost a family member. The findings indicate that these multifaceted losses substantially strained staff members’ ability to sustain their personal lives and academic responsibilities. These patterns reflect a systematic assault characterised as scholasticide—the targeted destruction of educators, academic environments, and the structures that sustain educational continuity—and educide, defined as the systemic dismantling of institutional infrastructure and educational continuity. This dual framework highlights how the destruction extends beyond incidental damage, aiming to erase educational continuity, community resilience, and academic identity in Gaza. Despite these challenges, UCAS staff demonstrated notable resilience. The study underscores the urgent need for global action to rebuild Gaza’s educational sector and to support displaced educators.